Fuzzy systems modeling of ease of doing business indicators - Roham, Mehrdad; Gabrielyan, Anait R.; Archer, Norman P.; McMaster eBusiness Research Centre (MeRC) (My University, 2008)
Ease of doing business (EDB) indicators are essential to the overall understanding and evaluation of national business environments, and to strategy formulations of business policy and regulations. The World Bank does an annual study of these indicators for over 170 nations, but there are many complications and uncertainties involved in their work. This paper proposes a new systematic approach that employs fuzzy set theory to generate composite EDB indicators for ranking and classification problems. In this paper, we implement the proposed approach and illustrate its process and procedures. A ... case study example for Canada is also presented in which EDB indicators are evaluated, linguistically identified, and ranked. This approach demonstrates the ease of using this fuzzy application, and its potential benefits for future research. We also compare ranking results, obtained from our proposed approach, with the World Bank's results.
56 p. ; Includes bibliographical references. ; "August 2008."
This work was supported by a grant from the Natural Sciences and Engineering Council of Canada.
Keywords: Fuzzy sets; Ease of doing business; Linguistic aggregation; Fuzzy ranking; Fuzzy systems > Simulation methods; Computer simulation; Economic indicators > Econometric models